All‐Inorganic CsPbX3 Perovskite Solar Cells: Progress and Prospects. Issue 44 (27th August 2019) - Zhang, Jingru; Hodes, Gary; Jin, Zhiwen; Liu, Shengzhong (Frank)
Abstract: Recently, lead halide‐based perovskites have become one of the hottest topics in photovoltaic research because of their excellent optoelectronic properties. Among them, organic‐inorganic hybrid perovskite solar cells (PSCs) have made very rapid progress with their power conversion efficiency (PCE) now at 23.7 %. However, the intrinsically unstable nature of these materials, particularly to moisture and heat, may be a problem for their long‐term stability. Replacing the fragile organic group with more robust inorganic Cs + cations forms the cesium lead halide system (CsPbX3, X is halide) as all‐inorganic perovskites which are much more thermally stable and often more stable to other factors. From the first report in 2015 to now, the PCE of CsPbX3 ‐based PSCs has abruptly increased from 2.9 % to 17.1 % with much enhanced stability. In this Review, we summarize the field up to now, propose solutions in terms of development bottlenecks, and attempt to boost further research in CsPbX3 PSCs. Abstract : Thermally stable and able : All‐inorganic CsPbX3 perovskites (X is halide) have attracted attention owing to their thermally stability for photovoltaic applications. This Review presents the various CsPbX3 materials and the challenges as well as perspectives for the future development of CsPbX3 solar cells.